2018
DOI: 10.1002/rob.21855
|View full text |Cite
|
Sign up to set email alerts
|

Low‐cost solution in international robotic challenge: Lessons learned by Tuscany Robotics Team at ERL Emergency Robots 2017

Abstract: European Robotics League (ERL) Emergency Robots is an outdoor robotics contest focusing on multidomain emergency response scenarios. In this context, the deployed robots are expected to fulfill land, underwater, and flying cooperative tasks which emulate real-world situations inspired by the 2011 Fukushima accident.Participation of the Tuscany Robotics Team at ERL Emergency Robots 2017 was deeply affected by damage to (and resulting unavailability of) the unmanned ground vehicle to be used in the competition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…in a robotic domain. Indeed, to the best of the authors' knowledge, few robotics research works have used this approach in their research ( [4,40]), still with a low number of robotic platforms. One possible direction of this work is to improve the proposed solution by adopting the current trends of networking approaches, such as the named-data-networking approach [41].…”
Section: Discussionmentioning
confidence: 99%
“…in a robotic domain. Indeed, to the best of the authors' knowledge, few robotics research works have used this approach in their research ( [4,40]), still with a low number of robotic platforms. One possible direction of this work is to improve the proposed solution by adopting the current trends of networking approaches, such as the named-data-networking approach [41].…”
Section: Discussionmentioning
confidence: 99%
“…It is an industrial competition focused on autonomous vehicles, which has prize money [3,4,27,33,35,39,53,59,62,66].…”
Section: Descriptionmentioning
confidence: 99%
“…The 2017 ERL Emergency competitions require flying, land and marine robots acting together to survey the disaster [53,54,66,74].…”
Section: Descriptionmentioning
confidence: 99%
“…It is shown that when solving the problems of object assignment, one can effectively use the power of an agent to achieve the targets. e article [14] provides an overview of the well-known works in this area of work. It is made the analysis of the problems of cooperative robots.…”
Section: Analysis Of Well-known Work With the Assignment Taskmentioning
confidence: 99%
“…erange characteristic of hitting the sword and the speed of the mobile objects are considered, as shown in Figure 11. e results of the solution in the third experiment are shown in Figures 12,13,and 14. e final decision on the appointment is summarized in Table 4.…”
Section: Experiments #mentioning
confidence: 99%